2003
DOI: 10.1017/s1138741600005175
|View full text |Cite
|
Sign up to set email alerts
|

Development of Memory Structures for Homographs Using Pathfinder Network Representations

Abstract: Some studies with children have shown that there is no semantic priming at short stimulus onset asynchrony (SOA) in lexical decision and naming tasks for homographs. The predictions of spreading activation theories might explain this missing effect. There may be differences in children's and adults' memory structures. We have explored this hypothesis. The development of memory structure representations for homographs was measured by a Pathfinder algorithm. In Experiment 1, the three dependent variables were: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This is an important difference since it is known that homographs are processed differently (Gorfein, 2001) and show less semantic facilitation (Milberg, Blumstein, & Dworetzky, 1987) than words with only one meaning. It is plausible that children showed no SPE when primes were homographs at shorter SOAs because they have differences in memory structure representations compared with adults (Nievas & Justicia, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This is an important difference since it is known that homographs are processed differently (Gorfein, 2001) and show less semantic facilitation (Milberg, Blumstein, & Dworetzky, 1987) than words with only one meaning. It is plausible that children showed no SPE when primes were homographs at shorter SOAs because they have differences in memory structure representations compared with adults (Nievas & Justicia, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, Frost and Bentin (1992) explicitly measured and controlled the degree of relation between prime and related targets. It is known that degrees of relation and associative strength are related (e.g., Experiment 3 in Nievas & Justicia, 2003); that is, the higher the degree of relation, the more associative strength. Other studies showed that an increase in associative strength produced an increase in positive priming (Cañas, 1990;Chiarello, Burgess, Richards, & Pollock, 1990;De Groot, Thomassen, & Hudson, 1982;Fischler, 1977;Lupker, 1984;Perea & Rosa, 2002).…”
mentioning
confidence: 99%